The Impact of Investors Overconfidence on Trading Activities and Stock Returns in Pakistan Stock Exchange - MUHAMMAD TAHIR KHAN; GHAYYUR QADIR; SHAH RAZA KHAN; ABDUL LATIF (Journal of Business & Tourism, 2021)
This study investigates the hypothesis of investor overconfidence that impact stock activity and stock return, using vector auto regressive model. Data observed consist of Monthly and daily returns from PSX 100 index. The results of the study shows that there are specific months in which the variables respond to each other or they are some actions that appears after some interval or else there is no significant relationship of current monthly return to past months volume, volume with volatility in stock returns as it is not increased with increase in volume. And there is no relationship of current monthly volume with previous market returns, Investor overconfidence has negative impact on trading activity as it keep them high and exaggerated level as it is not the real value of the securities and it may harm the investors. The results further marked that immediate past month return has an impact on current trading activity that is denoted from volume of trade.